The Influence of STEM-Based Learning on Vocational Students’ Higher-Order Thinking Skills: A Quasi-Experimental Study at SMKN 1 Boyolali - Suparmi; Budi Tri Cahyono (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The development of twenty-first-century education requires students to possess Higher-Order Thinking Skills (HOTS), including analytical, evaluative, and creative thinking abilities that are essential for addressing increasingly complex academic and workplace challenges. However, many vocational school students continue to demonstrate limited HOTS development due to the predominance of teacher-centered instructional practices that provide insufficient opportunities for inquiry, problem-solving, and active knowledge construction. This study aimed to examine the effect of STEM-based learning on students’ HOTS at SMKN 1 Boyolali. A quantitative approach employing a quasi-experimental design with a Pretest–Posttest Control Group Design was used. The study involved 214 students selected through simple random sampling, consisting of 107 students in the experimental group and 107 students in the control group. Data were collected using a HOTS essay test, classroom observations, and documentation. The instruments were validated through expert judgment and empirical testing, while data were analyzed using descriptive statistics, normality and homogeneity tests, independent samples t-tests, and N-Gain analysis with the assistance of SPSS version 29. The findings revealed a significant difference between the experimental and control groups, with a significance value of 0.000 (p < 0.05). Students in the experimental group achieved a higher mean posttest score (84.15) than those in the control group (72.36). Furthermore, the experimental group obtained an N-Gain score of 0.68 (moderate category), whereas the control group achieved 0.29 (low category). These findings indicate that STEM-based learning effectively enhances vocational students’ HOTS by promoting interdisciplinary problem-solving, collaboration, inquiry, and contextual learning experiences. The study contributes to the growing literature on STEM education by providing empirical evidence from a vocational education context and highlights the potential of STEM-based instruction to support the implementation of the Merdeka Curriculum and the development of workforce-relevant competencies.